2014
DOI: 10.5539/jfr.v4n1p22
|View full text |Cite
|
Sign up to set email alerts
|

Eating Difficulties, Nutrition, Meal Preferences and Experiences Among Elderly A Literature Overview From a Scandinavian Context

Abstract: The risk of malnutrition increases with ageing, resulting in poorer health and higher risk of disease. Eating difficulties are important risk factors for malnutrition. Moreover, independence in relation to food and meals is highly rated by the elderly and has been associated with health and well-being. The purpose of this literature overview was to provide insights into nutritional status, food choice and preferences as well as the meal situations of home-living elderly (65+) people with motoric eating difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 91 publications
2
25
0
1
Order By: Relevance
“…Chen (), Nyberg et al (), and Takei et al () described the importance of developing and enhancing new food products adapted to older consumers, in order to promote health and prevent malnutrition. It is important to assess the technological performance of such products.…”
Section: Resultsmentioning
confidence: 99%
“…Chen (), Nyberg et al (), and Takei et al () described the importance of developing and enhancing new food products adapted to older consumers, in order to promote health and prevent malnutrition. It is important to assess the technological performance of such products.…”
Section: Resultsmentioning
confidence: 99%
“…For example, these impairments can lead to slower wound healing and increase the risks of developing pneumonia and other infections, pressure ulcers, and fall injuries [13]. Furthermore, being able to eat, to enjoy food, and to participate in the social activities associated with meals are important aspects of the quality of life (QoL) for older people [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…The problems may also influence the ability to prepare food, set the table, handle and clean the plates and glasses (Gustafsson et al 2003) and, as a result, may affect total energy and nutrient intakes (McLaren and Dickerson 2000; Wylie, Copeman and Kirk 1999). Eating difficulties are described as an important risk factor for malnutrition among older people (Ekberg et al 2002; Maitre et al 2014; Nyberg et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also indicated lower quality of life as a result of eating difficulties (Acreman 2009; Jacobsson et al 2000; Tan and Fearon 2008). Eating difficulties, in combination with the endeavour to maintain independence, may result in nutritional problems, including the risk of becoming malnourished (Nyberg et al 2015).…”
Section: Introductionmentioning
confidence: 99%